Serving the Public Good?—A Corpus-Assisted Discourse Analysis of Private Prisons and For-Profit Incarceration in the United States - Marko, Karoline (Frontiers in Communication, 2021)
It is a well-known fact that the United States has a very high prison population compared to other countries, and that it is particularly the private prison industry that has been thriving (pond cummings & Lamparello, 2016). This industry is based on a for-profit ideology (Ortiz & Jackey, 2019) that aims to save money by cutting costs wherever possible (e.g. Burkhardt, 2017; Craig & pond cummings, 2020), and that, based on their profit-orientation, has no interest in rehabilitating offenders, since they make money with every incarcerated person (e.g. pond cummings & Lamparello, 2016). This paper investigates these issues from a linguistic perspective and takes a corpus of texts collected from the websites of the two largest private prison corporations in the United States (CoreCivic and The GEO Group) as a starting point for a corpus-assisted discourse analysis. The corpus comprises a total of 25,386 words and the analyses reveal that while both companies discursively background issues of violence, recidivism, and costs, they place a focus on the safety and security of their facilities and on their reentry programs for inmates. Thus, it is argued that the investigated corporations shift the discursive focus away from a negative discourse centering on violence and recidivism to a positive discourse centering on reentry and safety, which actively counters the findings that several researchers and journalists alike have revealed.